Lumpy price adjustments: a microeconometric analysis - Emmanuel Dhyne; Catherine Fuss; Mohammad Hashem Pesaran; Patrick Sevestre (Institute for the Study of Labor (IZA), 2007)
This paper presents a simple model of state-dependent pricing that allows identification of the relative importance of the degree of price rigidity that is inherent to the price setting mechanism (intrinsic) and that which is due to the price's driving variables (extrinsic). Using two data sets consisting of a large fraction of the price quotes used to compute the Belgian and French CPI, we are able to assess the role of intrinsic and extrinsic price stickiness in explaining the occurrence and magnitude of price changes at the outlet level. We find that infrequent price changes are not necessarily associated with large adjustment costs. Indeed, extrinsic rigidity appears to be significant in many cases. We also find that asymmetry in the price adjustment could be due to trends in marginal costs and/or desired mark-ups rather than asymmetric cost of adjustment bands.
urn:nbn:de:101:1-20080401372
Keywords: 330; Preisrigidität; Preis; Anpassung; Lebenshaltungsindex; Schätzung; Belgien; Frankreich